2016
DOI: 10.1002/jcph.749
|View full text |Cite
|
Sign up to set email alerts
|

Exposure‐Response Analysis of Sonidegib (LDE225), an Oral Inhibitor of the Hedgehog Signaling Pathway, for Effectiveness and Safety in Patients With Advanced Solid Tumors

Abstract: Sonidegib selectively inhibits smoothened protein, suppresses the growth of Hedgehog pathway-dependent tumors, and has recently been approved in the indication of locally advanced basal cell carcinoma. A comprehensive exposure-response analysis was conducted to further characterize the relationship of sonidegib exposure to efficacy and safety. Minimum observed plasma concentration at predose (C ), peak concentration (C ), and area under the curve were used as exposure endpoints. Exposure-efficacy analyses incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 17 publications
(45 reference statements)
1
13
0
Order By: Relevance
“…Following 4 weeks of treatment, Ber-EP4 and BCL-2 expression in tumors decreased, while HLA expression was upregulated on residual tumor cells, leading to the recruitment of CD8 + cytotoxic T cells into the tumor mass. Analysis with quantitative polymerase chain reaction revealed that expression of immune response-regulating genes was altered, which is consistent with our previous study that the Hh pathway is responsible for suppressing the immune response, and SMO antagonists relieve the suppression 52,53. Although this study was severely limited by the low number of patients treated with sonidegib, the result supports the role of Hh signaling for the immune suppressive microenvironment as well as the possibility to combine immune modifiers with Hh signaling inhibition to achieve extended tumor control.…”
Section: Clinical Trials With Sonidegibsupporting
confidence: 91%
See 2 more Smart Citations
“…Following 4 weeks of treatment, Ber-EP4 and BCL-2 expression in tumors decreased, while HLA expression was upregulated on residual tumor cells, leading to the recruitment of CD8 + cytotoxic T cells into the tumor mass. Analysis with quantitative polymerase chain reaction revealed that expression of immune response-regulating genes was altered, which is consistent with our previous study that the Hh pathway is responsible for suppressing the immune response, and SMO antagonists relieve the suppression 52,53. Although this study was severely limited by the low number of patients treated with sonidegib, the result supports the role of Hh signaling for the immune suppressive microenvironment as well as the possibility to combine immune modifiers with Hh signaling inhibition to achieve extended tumor control.…”
Section: Clinical Trials With Sonidegibsupporting
confidence: 91%
“…Both responders and nonresponders showed similar plasma concentration levels, but there was no correlation between the dosage and probability of tumor response. Similarly, increasing exposure did not show an improvement in progression-free survival nor in time to tumor response 52. Thus, patients who fail to respond to lower doses may not benefit from an increase in dose.…”
Section: Clinical Trials With Sonidegibmentioning
confidence: 90%
See 1 more Smart Citation
“…Previously published population PK and exposure‐toxicity models of sonidegib were used to simulate (n = 100) scenarios of taking sonidegib in different ways with respect to food . It was known that sonidegib had a 5‐ to 7‐fold increase in exposure with a high‐fat, high‐caloric meal.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, a 2‐compartment model with first‐order absorption with lag‐time, linear elimination, and bioavailability that increased by 5.74‐fold in fed condition was used to simulate the steady state trough plasma concentration on cycle 2 day 1 of sonidegib therapy . This simulated PK metric was used in an exposure‐toxicity model to drive the probability of developing a grade 3/4 creatine kinase (CK) elevation according to Equations and , logπfalse(normalxfalse)πfalse(normalxfalse)+1=β0+β1·normalCtrueprefixmin/100+β2· Sex πfalse(normalxfalse)=exp(β0+β1·Cmin+β2· Sex )1+exp(β0+β1·Cmin+β2· Sex )where π(x) is the probability of developing grade 3/4 CK elevation, β 0 , β 1 , and β 2 are the intercept (−2.58) and slopes (0.10 for C min and −0.92 for female) in the logistic regression, and C min is the steady‐state trough plasma concentration (ng/mL) on cycle 2 day 1.…”
Section: Methodsmentioning
confidence: 99%